Cost-Effectiveness of Ipilimumab Plus Anti-PD-1 Therapy Versus Ipilimumab Alone in Patients With Metastatic Melanoma Resistant to Anti-PD-(L)1 Monotherapy - Peng, Ye; Zeng, Xiaohui; Peng, Liubao; Liu, Qiao; Yi, Lidan; Luo, Xia; Li, Sini; Wang, Liting; Qin, Shuxia; Wan, Xiaomin; Tan, Chongqing (Frontiers in Oncology, 2021)
Objective The use of ipilimumab plus anti-PD-1 has recently been shown to significantly improve the survival of patients with metastatic melanoma resistant to anti-PD-(L)1 monotherapy. The study assessed the cost-effectiveness of ipilimumab plus anti-PD-1 therapy in this population from the US payer perspective. Materials and Methods A Markov model was created based on a retrospective analysis of patients with metastatic melanoma who were resistant to anti-PD-(L)1. Cost information was obtained from the Centers for Medicare and Medicaid Services and literature-based costs. The utility value was derived from the published literature. The results of the model was the total cost, quality-adjusted life-year (QALY), and incremental cost-effectiveness ratio (ICER). The uncertainty of the model was addressed through sensitivity analysis. In addition, we also conducted subgroup analysis. Results Ipilimumab plus anti-PD-1 provided an improvement of 1.39 QALYs and 2.48 LYs, at a ICER of $73,163 per QALY. The HR of OS was the variable that had the greatest impact on ICER. Compared to ipilimumab, the probability of ipilimumab plus anti-PD-1 being cost-effective was 94% at the WTP of $150,000/QALY. The results of the subgroup analysis showed that the ICER in the majority of the subgroups was less than $150,000/QALY. Conclusions Ipilimumab plus anti-PD-1 was likely to be cost-effective compared to ipilimumab for patients with metastatic melanoma who are resistant to anti-PD-(L)1 at a WTP threshold of 150,000/QALY.